Clinical course and outcomes of COVID-19 patients with chronic obstructive pulmonary disease: A retrospective observational study in Wuhan, China. Issue 18 (6th May 2022) - Bai, Yang; Wen, Liang; Zhao, Yulong; Li, Jianan; Guo, Chen; Zhang, Xiaobin; Yang, Jiaming; Dong, Yushu; Ma, Litian; Liang, Guobiao; Kou, Yun; Wang, Enxin
Abstract : Abstract: Information about coronavirus disease 2019 (COVID-19) patients with pre-existing chronic obstructive pulmonary disease (COPD) is still lacking. The aim of this study is to describe the clinical course and the outcome of COVID-19 patients with comorbid COPD. This retrospective study was performed at Wuhan Huoshenshan Hospital in China. Patients with a clear diagnosis of COVID-19 who had comorbid COPD (N = 78) were identified. COVID-19 patients without COPD were randomly selected and matched by age and sex to those with COPD. Clinical data were analyzed and compared between the two groups. The composite outcome was the onset of intensive care unit admission, use of mechanical ventilation, or death during hospitalization. Multivariable Cox regression analyses controlling for comorbidities were performed to explore the relationship between comorbid COPD and clinical outcome of COVID-19. Compared to age- and sex-matched COVID-19 patients without pre-existing COPD, patients with pre-existing COPD were more likely to present with dyspnea, necessitate expectorants, sedatives, and mechanical ventilation, suggesting the existence of acute exacerbations of COPD (AECOPD). Greater proportions of patients with COPD developed respiratory failure and yielded poor clinical outcomes. However, laboratory tests did not show severer infection, over-activated inflammatory responses, and multi-organ injury in patients with COPD. Kaplan–Meier analyses showed patients with COPD exhibited longer viral clearance time in the respiratory tract. Multifactor regression analysis showed COPD was independently correlated with poor clinical outcomes. COVID-19 patients with pre-existing COPD are more vulnerable to AECOPD and subsequent respiratory failure, which is the main culprit for unfavorable clinical outcomes. However, COPD pathophysiology itself is not associated with over-activated inflammation status seen in severe COVID-19.